Physical Activity Siswa SMA Negeri 3 Purwakarta di Masa Pandemi Covid-19 - Putri Dwi Renti; Febi Kurniawan; Fahrudin Fahrudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
Abstract As written on the background in the study, the purpose of this study was to determine the physical activity of SMAN 3 Purwakarta students during the covid-19 pandemic for one week. This research is a descriptive research in the form of quantitative data, the method used in this research is a survey method using random sampling technique. Another term for random sample is one in which all individuals in the target population have an equal opportunity to choose. The population in this study were all students of class XI IPA SMAN 3 Purwakarta, totaling 160 students. Based on the results of the study, the percentage that the physical activity of SMAN 3 Purwakarta students during the Covid-19 pandemic was male students in the "very low" category was 5.50% (1 student), "low" was 16.60% (3 students), “enough” 33.30% (6 students), “high” 33.30% (6 students), and “very high” 11.11% (2 students). While the level of physical activity of SMAN 3 Purwakarta students during the Covid-19 pandemic, female students were in the "very low" category 9% (4 students), "low" 15.90% (7 students), "enough" 36.30% (16 students), “high” 31.80% (14 students), and “very high” 6.80% (3 students). It can be concluded that overall most of the male students of class XI Science 1 and 3 of SMAN 3 Purwakarta do physical activity in the high category, which is 33.30% (12 students), while the female students do the most physical activity in the "enough" category 36, 30% (16 students).